Comparative Study of Restorative Justice with The Concept of Al-'Afwu in Criminal Offenses - Rini Eka Agustina; M. Junaidi (Proceeding International Conference Restructuring and Transforming Law, 2024)
The aim of this research is to determine the difference between the concept of restorative justice and al-'afwu in criminal acts. The type of research used is descriptive qualitative research with a library research approach. Data analysis uses the Miles and Huberman model which states that data analysis includes data reduction, data presentation and drawing conclusions. Primary data sources are taken from the Criminal Code and secondary data sources from books, journals and other relevant references. From the analysis of existing data, the following research results were obtained: (1) the type of criminal behavior in restorative justice is classified as a lighter crime level, while al-'afwu is classified as a serious crime level, such as murder and assault. (2) compensation for losses, restorative justice receives compensation in the form of material or money. while al-'afwu compensates for the loss with diyat which compensates the loss in the form of property to the victim as compensation for the loss. (3) the aim of criminal punishment, restorative justice does not only focus on the perpetrator, but also looks at the recovery of the victim, the perpetrator of the crime, and involves community participation. pays attention to the process of healing, reconciliation and reintegration, while al-'afwu prioritizes preventing damage/misfortune in human life, and revenge as a reward for the perpetrator's actions with the aim of preventing crime.